PERBANDINGAN PENGATURAN TINDAK PIDANA PENODAAN AGAMA DI INDONESIA DENGAN PAKISTAN (TINJAUAN BERDASARKAN MIXED LAW SYSTEM) - Silaban, Marthin Adolf Alexander (Honeste Vivere, 2025)
Indonesia and Pakistan are presently among the nations that criminalize blasphemy. Both nations are the largest Muslim-majority countries globally. Notably, the regulation of blasphemy varies significantly between the two countries. This study was conducted in a normative legal framework. The findings reveal that the disparities in blasphemy regulations between Indonesia and Pakistan are influenced by each country's legal heritage and historical context. Although both are classified as mixed legal systems, Indonesia's legal framework is dominated by civil law, whereas Pakistan legal system is dominantly shaped by Islamic law along with the common law system derived from England. In Indonesia, blasphemy is addressed under Article 156a KUHP, UU PNPS, and UU ITE, imposing penalties of imprisonment and/or fines. In contrast, Pakistan's legislation comprises numerous articles that specifically criminalize blasphemy across various classifications, imposing severe penalties including the death penalty, life imprisonment, and specific terms of incarceration, often accompanied by fines. In comparison, Indonesia's criminal act of religious blasphemy aligns more closely with human rights principles and is less discriminatory compared to Pakistan Penal Code